Primary Spontaneous Pneumothorax In Healthy Tall and Thin Male Secondary to Smoking: A Case Report and Literature Review - Budi Yanti; Rina Marlena (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2023)
Background: Primary Spontaneous Pneumothorax (PSP) refers to the collapse of a lung without any underlying disease and is commonly observed in tall, thin young men, with smoking as an under-recognized risk factor. The management of PSP can vary significantly across different health centers. This case report highlights a young man with a pneumothorax without an underlying illness but has a smoking habit who initially gets treatment with an insertion of a chest tube.Case: This study focused on a 19-year-old man complaining of sudden right chest pain. The patient was a smoker for the past four years, and the examination showed hypersonic and vesicular loss on the right side. The laboratory tests revealed normal limits, and the sputum indicated the absence of tuberculosis. Chest X-ray showed an avascular radiolucent area in the right lung, and a Chest CT scan confirmed the presence of a hypodense area of air density in the right hemithorax. Right PSP was diagnosed and managed using a chest tube drainage on admission. After four days of treatment, he exhibited improvement and was discharged. A recurrence of pneumothorax was not discovered in the subsequent six-month follow-up period.Conclusion: Despite being a rare disorder, PSP should be considered during the physical examination of patients. It is also important to reassess the risk factors that can contribute to the onset of pneumothorax. The clinicians should be able to identify PSP and emphasize tall, thin, and young men at greater risk of pneumothorax in a pulmonary emergency.